Manajemen Konflik Pada Tatanan Pelayanan Keperawatan Di Rumah Sakit: Literature Review - Ana Fitrianingsih; Alya Huwaida Anjani; Neng Inggri Fitriya; Puspa Dewi Anggraini; Heri Ridwan; Ahmad Purnama (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
ABSTRAK Backgorund: The majority of healthcare professionals who offer services in hospitalsare nurses. However, nurses frequently neglect interprofessional partnerships and teamwork in favor of concentrating solely on their individual jobs. This may lead to conflict inside a healthcare organization, which may have an impact on the efficiencywith which nurses provide nursing care. Purpose: The purpose of this literature review is to identify factors that have the potential to cause conflict, the parties involved in conflict management, conflict management strategies or solutions in the nursing workplace, and variables that influence the success of conflict resolution. Methods: A literature review was used as a method in this research. The scientific databases used are Google Scholar, Sage Journals, PubMed, Elsevier, Wiley, BookedCentral,andPortal Garuda. The search results yielded 92 articles.After selection,there were 11 international journal articles and 14 national journal articles. The selection process uses an abstract checklist and a PRISMA checklist. Result: The results of the review show that the factors that cause conflict in health services include work stress, low work satisfaction and motivation, miscoordination a lack of empathy in interdisciplinary collaboration and toxic leadership. The parties involved in conflict resolution are the head of the room, nurse manager, nurses and doctors. Conflict resolution can be carried out with compromising, integrating,cooperative, assertive and obliging strategies which are supported by interdisciplinary communication, management skills, emotional intelligence and the involvement of clinical educators. Conclusion:The aspects that most often cause conflict are work stress and problems with work coordination and interdisciplinary collaboration. The parties most often involved are the head of the room and the nurse manager. Conflict management can be done using an integrating style, where the integrating style is also the most dominant style of conflict management strategy. Mindfulness is a supporting factor in implementing this integrating style. Key words: Conflict Management; Hospital; Nursing; Related parties; Strategy Issues.